2016
DOI: 10.1016/j.biomaterials.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Toward carbon nanotube-based imaging agents for the clinic

Abstract: Among the many applications for carbon nanotubes (CNTs), their use in medicine has drawn special attention due to their potential for a variety of therapeutic and diagnostic applications. As progress toward clinical applications continues, monitoring CNTs in vivo will be essential to evaluate their biodistribution, potential toxicity, therapeutic activity, and any physiological changes that the material may induce in specific tissues. There are many different imaging modalities to visualize and track CNTs in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 126 publications
0
28
0
Order By: Relevance
“…Engineered CNTs are able to act as excellent adjuvant Contrast Agents (CA) for many different imaging techniques [42] and to enhance drug cytotoxicity [43]. Moreover, they can be used to perform thermal ablation [44], as well as to detect Reactive Oxygen Species (ROS) [45] or specific antigens, likewise tumor markers [46].…”
Section: Cnts and Cancermentioning
confidence: 99%
“…Engineered CNTs are able to act as excellent adjuvant Contrast Agents (CA) for many different imaging techniques [42] and to enhance drug cytotoxicity [43]. Moreover, they can be used to perform thermal ablation [44], as well as to detect Reactive Oxygen Species (ROS) [45] or specific antigens, likewise tumor markers [46].…”
Section: Cnts and Cancermentioning
confidence: 99%
“…19,20 SWCNTs exhibit photostable, intrinsic photoluminescence in the near infrared (NIR) spectral window 21 where there is minimal absorption, autofluorescence, and scattering of light in biological specimens. 22 Therefore, SWCNTs are promising for the study of cellular transport processes.…”
mentioning
confidence: 99%
“…Carbon nanomaterials have been found to be an excellent scaffold for contrast agents since they can be used to carry imaging agents, such as fluorescent labels and radionuclides, contributing to the generation of high-quality images and the early detection of breast cancer [20,21,49,[56][57][58]. Experiments have demonstrated that CNT can carry imaging agents [57] and demonstrated great potential of using functionalized MWCNT as efficient cell probes for MRI [59].…”
Section: Contrast Agentmentioning
confidence: 99%
“…Experiments have demonstrated that CNT can carry imaging agents [57] and demonstrated great potential of using functionalized MWCNT as efficient cell probes for MRI [59]. In vivo MRI on mice showed that CNTs functionalized with Gd (GdCNTs) have the ability to act as a good contrast agent [60].…”
Section: Contrast Agentmentioning
confidence: 99%
See 1 more Smart Citation